Microtensile bond strength of a universal adhesive to deep dentin - Gre, Cristina; Amaral Caldeira de Andrada, MAuro; Monteiro Junior, Sylvio (Brazilian Dental Science, 2016)
Objective: This study evaluated the microtensile bond strength of a universal adhesive system applied to deep dentin under different bonding strategies. Material and Methods: Fifteen human third molars had the coronal portion removed exposing deep dentin and were assigned into 3 groups according to the adhesive system: G1(control): 2-steps totaletch (Adper Single Bond 2, 3M ESPE); G2: 1-step self-etch universal adhesive (Scotchbond Universal, 3M ESPE); G3:2 steps total-etch universal adhesive (Scotchbond Universal, 3M ESPE). Composite buildups were performed on the dentin surfaces and after water storage for 24 h, teeth were sectioned to obtain 40 bonded beams per group with sectional area of 0.9 mm2 . The specimens were submitted to the microtensile bond strength (µTBS) test until failure. Statistical analyses were computed using one-way ANOVA (p = 0.05). Results: The mean µTBS (in MPa) were G1 = 22.27, G2 = 22.85 and G3 = 20.3. After statistical analysis, no significant differences were observed among the groups. Conclusions: Universal adhesive system performed similarly to the total-etch adhesive and was not affected by the adhesion strategy. KEYWORDS Microtensile; Adhesive system; Dentin.